Pulmonary echinococcosis in China - Mao, Teng; Chungda, Dawa; Phuntsok, Lhakpa; Benjie, Tse; Dondrup, Tsering; Dolma, Tseten; Li, Weijiang (Journal of Thoracic Disease, 2019)
Pulmonary echinococcosis is a zoonotic parasitic disease caused by the larval stage of cestodes belonging to the genus echinococcus, which is the top killer of residents in pastoral areas and requires more attention. Prevention is the top priority; screening is another important strategy. Surgery is still the preferred treatment for pulmonary echinococcosis. Fortunately, the Chinese government has equipped each county hospital with CT machines. In the foreseeable future, the screening for pulmonary echinococcosis will begin in many areas including Tibet, which will allow us to cure early pulmonary echinococcosis in a more minimally-invasive way.